AKREDITASI SEBAGAI PERTANGGUNGJAWABAN INSTITUSI TERHADAP STAKEHOLDER - touvan samodra; Sesilia Seli; Lily Thamrin; Asriah Nurdini Mardiyaningsih; Uray Gustian; Rio Pranata; Dwi Riyanti; Putri TipaAnasi; Dian Miranda (UHN IGB Sugriwa Denpasar, 2023)
Higher education's internal quality assurance system (IQAS) has regulated both the mechanism and the final achievement. To provide quality educational services, one of the pieces of evidence is the existence of an accreditation level status. The accreditation level status results from a quality culture reflected in good reporting following the planned conditions and achievements achieved. This effort is not wholly running smoothly. The change of different criteria in the output-based BAN-PT Accreditation is a challenge that forces a change in work patterns and reporting. Availability of standards, output targets, and outputs must be measurable in each criterion. Several things are still obstacles, so that the implementation of IQAS is significantly related to achievement standards, ease of accessing information, and document renewal which must adjust changes to the nine criteria. IQAS's efforts were carried out as preparation for external quality assurance as an institution's accountability to stakeholders.